2018
DOI: 10.1182/blood-2017-10-813493
|View full text |Cite
|
Sign up to set email alerts
|

ADCT-402, a PBD dimer–containing antibody drug conjugate targeting CD19-expressing malignancies

Abstract: Human CD19 antigen is a 95-kDa type I membrane glycoprotein in the immunoglobulin superfamily whose expression is limited to the various stages of B-cell development and differentiation and is maintained in the majority of B-cell malignancies, including leukemias and non-Hodgkin lymphomas of B-cell origin. Coupled with its differential and favorable expression profile, CD19 has rapid internalization kinetics and is not shed into the circulation, making it an ideal target for the development of antibody-drug co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
110
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 142 publications
(118 citation statements)
references
References 33 publications
8
110
0
Order By: Relevance
“…Two anti-CD19 ADCs (SGN-CD19B and ADCT-402) using PBD dimer payload are currently in phase I clinical trials. ADCT-402 shows an encouraging complete RR of 34.3% so far, which is comparable to phase I data from denintuzumab mafodotin and coltuximab ravtansine (payloads = anti-microtubule agents) [65]. …”
Section: Introductionsupporting
confidence: 68%
“…Two anti-CD19 ADCs (SGN-CD19B and ADCT-402) using PBD dimer payload are currently in phase I clinical trials. ADCT-402 shows an encouraging complete RR of 34.3% so far, which is comparable to phase I data from denintuzumab mafodotin and coltuximab ravtansine (payloads = anti-microtubule agents) [65]. …”
Section: Introductionsupporting
confidence: 68%
“…The clinical activity for ADCT-402, a CD19-targeted ADC with a pyrrolobenzodiazepine payload, will help to address this question. 47 In conclusion, this study has shown that denintuzumab mafodotin is active against pediatric ALL PDXs, both as a single agent and in combination with an induction therapy platform. However, the level of activity does not distinguish itself from that of vincristine as a single agent.…”
Section: Discussionmentioning
confidence: 68%
“…Does the lack of clinical activity comparable to that of other ALL immunotherapy approaches indicate that CD19 is a poorer target for ADCs compared to other lymphoid surface antigens possibly due to less efficient CD19 internalization compared with, for example, CD22? Alternatively, is the limited activity related to the tubulin‐binding cytotoxic payload? The clinical activity for ADCT‐402, a CD19‐targeted ADC with a pyrrolobenzodiazepine payload, will help to address this question …”
Section: Discussionmentioning
confidence: 99%
“…117 Loncastuximab tesirine (ADCT-402) is a novel CD19-targeted ADC that delivers SG3199, a highly cytotoxic pyrrolobenzodiazepine dimer, and showed highly targeted cytotoxicity in vitro and antitumor activity in vivo in preclinical studies. 118 A pivotal phase 2 study (NCT03589469) is currently ongoing on relapsed or refractory DLBCL, as well as phase 1 studies (NCT02669017, NCT03684694, and NCT03685344) on relapsed or refractory B-NHLs.…”
Section: Cd19mentioning
confidence: 99%